The hematological parameters in clinically normal Iraqi local breed goats: AL-dujaily A.H.1 and AL-Hadithy H.AH.2 - AL-Hadithy, AH. H. (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of the present work is to determine the hematological parameters in clinically normal local breed goats. The study was conducted on 130 goats (40 males of them 20 bucks and 20 buck kids and 90 females of them 20 doe kids, 20 dry does, 25 pregnant and 25 lactating does) aged 6 months-4 years in AL-Najaf province-Iraq. Blood samples were collected from the jugular vein into EDTA tubes during October 2013 untill February 2014. Results showed that the ranges and means ±SE of blood picture were as follows; packed cell volume (PCV) 26-40% and 31.8±0.32%, Hemoglobin (Hb) 8-14.3g/dL and 10.3±0.13 g/dL, Red blood cell (RBC) 10.6-17×106/μL and 13.3±0.14×106/μL, Mean cell volume (MCV) 18.4-32.5 fL and 23.9±0.14 fL, Mean cell Hemoglobin (MCH) 5.5-8.8 and 7.7±0.05 pg, Mean cell hemoglobin concentration (MCHC) 28.3-36.9 g/dL and 32.4±0.15 g/dL, Erythrocyte sedimentation (ESR) 1-10 mm/ 24h and 4.1±0.14 mm/ 24h, White blood cell count (WBC) 5500-15900/μL and 10732±242/μL, Lymphocyte (L) 2772-10172/μL and 6080±149 /Μl, neutrophils (N) 1863-8680/μL and 4112±121/μL, monocytes 57.0-622/μL and313±11/μL, eosinophil’s 0-918/μL and 222±14/μL, basophils 0±0/μL and 0±0/μL, L/N ratio 0.4-3.8 and 1.5±0.04, respectively. There was a significant (P<0.05) increase in PCV, Hb, RBC, MCV, MCH, MCHC and no difference in ESR,WBC, DLC and L/N ratio between males and females. However, significant (P<0.05) differences in most hematological parameters of sub groups have been recorded. In conclusion the present data recorded the reference values of hematological parameters in clinically healthy local breed goats with a significant difference between males and females as well as in normal subgroups.